1999
DOI: 10.1023/a:1006985700851
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Smokeless tobacco usage is a growing public health concern in the United States. Lesions of the oral cavity have been clearly linked to smokeless tobacco use. The objective of this study was to determine the biochemical effects of smokeless tobacco extract (STE) exposure upon hamster cheek pouch cell (HCPC-1) cultures. HCPC-1 cells were exposed to a 5 -fold dose-range of STE (0.5, 1.0 and 2.5%) over a time-course of 24-96 h. Following each exposure we measured various biochemical parameters of cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…We were unable to see any apoptotic induction with the treatment before 24 h at the protein level. This finding is in line with a report that showed that induction of apoptosis with the same product (1S3) started from 48 h and remained as so until 96 h suggesting STE induced apoptosis is a late event [18].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We were unable to see any apoptotic induction with the treatment before 24 h at the protein level. This finding is in line with a report that showed that induction of apoptosis with the same product (1S3) started from 48 h and remained as so until 96 h suggesting STE induced apoptosis is a late event [18].…”
Section: Discussionsupporting
confidence: 93%
“…Mechanistically, the induction of apoptosis as a result of STE exposure was suggested to be associated with the modulation of nitric oxide [18], oxidative stress [16], and osmotic stress [37]. Components in STE are implicated in the activation of Cytochrome-c, an activator of the intrinsic pathway of apoptosis, with the production of superoxide anions [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mangipudy and Vishwanatha [ 53 ] reported that smokeless tobacco extract causes a dose-dependent activation of apoptosis through the immediate actions of nitric oxide. We examined the participation of anti-apoptotic and pro-apoptotic markers, which have been described as importantly involved in the process of apoptosis.…”
Section: Discussionmentioning
confidence: 99%